KOMUNIKASI BUNDO KANDUANG DALAM TRADISI BARARAK SAMBA 12 DI NAGARI SULIT AIR KAB.SOLOK - Fitri, Winda Utari; Syafriwaldi (KINEMA: Jurnal Komunikasi dan Penyiaran, 2025)
This study explores the verbal and non-verbal communication of Bundo Kanduang in the Bararak Samba 12 tradition in Nagari Sulit Air, Solok Regency. As an integral part of the traditional wedding procession, the tradition embodies cultural values and rich symbolism. Within this context, Bundo Kanduang serves as the primary communicator, delivering customary messages through meaningful verbal expressions and symbolic non-verbal cues. The analysis employs Wilbur Schramm’s communication theory to examine verbal communication as a two-way process shaped by cultural background and personal experience, while Onong Uchjana Effendy’s framework is applied to assess non-verbal communication forms such as gestures, facial expressions, and traditional symbols. This qualitative field research utilized observation, interviews, and documentation, with source and method triangulation ensuring data validity. The findings reveal that verbal communication reflects local wisdom through distinctive traditional language, whereas non-verbal communication is conveyed through gestures, expressions, and symbolic objects. Both forms function not only to convey information but also to maintain social harmony, reinforce collective identity, and instill social and ethical values. Consequently, communication in the Bararak Samba 12 tradition serves as a vital medium for preserving Minangkabau cultural heritage.